Uji Kualitas Kertas Seni Berbahan Dasar Sabut Kelapa Dan Limbah Kulit Kacang Tanah Melalui Proses Organosolv - Purwanti, Purwanti, Dra. Aminah Asngad, M.Si (2017)
Coconut husk and peanut shell waste are the example of agricultural waste that are very abundant and rarely used. Coconut husk and peanut shell waste are the basic materials for making art paper because coco husk contains fiber content and peanut shell contains cellulose and lignin. The aim of the study is to determine the tensile strength, tear resistance, and sensory test of art paper from coconut husk and peanutshell waste. This research used experimental method with Completely Randomized Design (RAL) with two factors of treatments, as follows : 1. comparison of material composition. (A), A1: 50%: 50%, A2: 60% : 40% , 2. ethanol solvent amount (B), B1: 1250 ml ethanol (1:25) , B2: 1500 ml of ethanol (1:30), and B3: ethanol 1750 ml (1:35), each treatment was repeated twice.Data collection techniques in this study is descriptive qualitative. The research shows the highest result of tensile strength and tear resistance were found in A2B3 treatment (60%: 40%, ethanol 1750 ml) with of 1,462 N / mm2 and 1.6650 Nfor highest tear resistance. The results of sensory tests are the highest texture of art paper on A2B1 treatment which is rough, the appearance of highest fiber of A1B1 and A2B1 treatment (visible), the highest color of A1B3 and A2B3 trearment (brown), and the community's satisfaction of the highest art paper on A1B3 and A2B3 treatments. The differences of tensile resistance, tear resistance and sensory character of art paper are caused by several factors affecting on paper production.